My hero academia 1 - Horikoshi, Kohei, 1971- (San Francisco, CA : VIZ Media, LLC, 2020)
"A villain incident when Aizawa was a student at U.A. changed him forever. Who could have known that fateful encounter would someday have an impact on the present? But as time goes by, life also changes for Koichi, Pop, Makoto and everyone else. The glory days of Narufest are over, and it's time to move on. Makoto puts an important question to Koichi, and Pop struggles to find herself. But Pop's decision to go it alone may lead her down a dangerous path"--Back cover.
"First published in Japan in 2016 by Shueisha Inc., Tokyo"--Colophon.
"Original concept: Kohei Horikoshi."
"Rated T Teen"--Back cover.
This book reads from right to left in the traditional Japanese format.
Translated from the Japanese.
5-8.
Keywords: College students -- Comic books, strips, etc -- Juvenile fiction; Superheroes -- Comic books, strips, etc -- Juvenile fiction; Supervillains -- Comic books, strips, etc -- Juvenile fiction; Vigilantes -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; College students -- Fiction; Superheroes -- Fiction; Supervillains -- Fiction; Vigilantes -- Fiction; College students -- Comic books, strips, etc -- Fiction; Manga; Superhero graphic novels; Superheroes -- Comic books, strips, etc -- Fiction; Supervillains -- Comic books, strips, etc -- Fiction; Vigilantes -- Comic books, strips, etc -- Fiction; Graphic novel adaptations; Graphic novels; Superhero comics